(untitled) - Macfarlane, Mike (Oxford, 1998)
A two-level general English course designed specifically for working adults at pre-intermediate and intermediate level. The emphasis is on covering the English they will need for work, travel, and socializing, by the use of serious, high-interest materials which will appeal to busy professionals.
Keywords: English language,English language; Study and teaching - problems, exercises, etc,Textbooks for foreign speakers